Studi kasus klasik dalam psikologi / Geoff Rolls ; penerjemah, Helly Prajitno Soetjipto, Sri Mulyantini Soetjipto. - ROLLS, Geoff; Helly Prajitno Soetjipto; Sri Mulyani Soetjipto (Pustaka Pelajar, 2012)
xviii, 404 hlm. : ilus ; 23 cm (3 eks.)